Attachment Styles and Emotional Connectivity in Indonesian Long Distance Relationships: A Cultural Phenomenological Study - Subiantoro, Anjar (Indonesian Scientific Publication, 2025)
This study examines how adult attachment styles shape relationship satisfaction among Indonesian university students in long distance romantic relationships (LDRs). Using a qualitative phenomenological design with seven participants aged 20–24, the research explored lived experiences of communication, intimacy, trust, and cultural values. Findings revealed that securely attached individuals displayed consistent communication, emotional openness, and resilience, whereas avoidant and fearful-avoidant individuals struggled with self-disclosure, emotional closeness, and satisfaction. Indonesian collectivist norms moderated attachment expressions, emphasizing emotional restraint and family-oriented decision making. The study highlights the cultural adaptation of attachment theory, showing how trust and intimacy are mediated by sociocultural expectations and digital communication. Practical implications include the need for culturally tailored therapeutic interventions, such as Emotionally Focused Couple Therapy (EFCT) and teletherapy. Future research should involve more diverse samples and longitudinal or mixed-method designs to deepen understanding.